High-Sensitive Cardiac Troponin I and Th1/Th2 Polarization in Queens With Pyometra - Safak, Tarik; Saat, Nevzat; Yilmaz-Koc, Oznur; Turanli, Mert; Ayalp-Erkan, Aslihan; Risvanli, Ali (Wiley, 2025)
Objectives: To determine T helper (Th)1 and Th2 cytokine polarization, as well as high-sensitive cardiac troponin I (hs-cTnI) levels, in cats with pyometra. Methods: We used 40 queens in the study. A total of 20 out of these 40 queens were diagnosed with the pyometra group (PYO) and the other 20 made up the healthy group (control; CTR). We measured concentrations of hs-cTnI, aspartate aminotransferase (AST), creatine kinase (CK) and l-lactate in queens from both groups. Additionally, we measured cytokine concentrations in all queens. Results: The hs-cTnI concentration in the PYO group (26.95 +/- 5.08 ng/L) was significantly higher than that of the CTR group (7.00 +/- 0.82 ng/L) (p < 0.000). Furthermore, the PYO group had a higher CK concentration (344.50 +/- 39.63 U/L) than the CTR group (191.00 +/- 15.44 U/L) (p = 0.002). The PYO group also demonstrated higher concentrations of TNF-alpha (9.77 +/- 0.81 ng/mL), IFN-gamma (25.37 +/- 2.09 ng/mL), IL-2 (4.37 +/- 0.39 ng/mL), IL-4 (245.64 +/- 15.83 pg/mL), IL-5 (63.13 +/- 1.65 pg/mL) and IL-10 (123.58 +/- 4.30 ng/mL) compared to the CTR group (p < 0.000). Conclusions: Overall, it is suggested that changes in cytokine concentrations increase in queens with pyometra, potentially causing harm to the heart muscle. It is crucial to consider that the heart muscle may also be affected in queens with pyometra during the treatment process.
Keywords: high-sensitive cardiac troponin I; pyometra; queen; Th1/Th2 cytokine polarization